Method for analyzing formula of heat-conducting powder in heat-conducting material

The particle size distribution test was carried out after solid-liquid extraction and hydrofluoric acid treatment, and combined with fitting analysis, the efficiency and accuracy of powder particle size formula analysis in thermally conductive materials were solved, and a fast and accurate powder formula analysis was achieved.

CN119290684AActive Publication Date: 2025-01-10HUBEI DINGHUI MICROELECTRONICS MATERIALS CO LTD +2
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411548768.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-10
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and accurately analyze the particle size formula of thermally conductive powders in thermally conductive materials, resulting in low analysis efficiency and inaccurate results.

Method used

Particle size distribution test was carried out after solid-liquid extraction and hydrofluoric acid treatment, and combined with fitting analysis, a particle size distribution curve was constructed to determine the formula of the thermally conductive powder.

Benefits of technology

Quantitative analysis of powder formula in thermally conductive materials is realized, which improves the accuracy and efficiency of the analysis, reduces errors and is convenient to operate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0005114513500000051
    Figure BDA0005114513500000051
  • Figure HDA0005114513520000011
    Figure HDA0005114513520000011
Patent Text Reader

Abstract

The invention relates to a method for analyzing a formula of heat-conducting powder in a heat-conducting material, which comprises the following steps of: performing solid-liquid extraction on the heat-conducting material by using an organic solvent, and filtering and separating filtrate and solid residues; hydrofluoric acid is added into the solid residues, filtering is performed after sufficient stirring, and dried powder is obtained after filter cakes are washed and dried; carrying out particle size distribution test on the dried powder to obtain a particle size distribution curve, and determining each peak in the particle size distribution curve and the corresponding particle size classification so as to determine the median particle size of each single-particle-size powder in the powder; performing particle size distribution test on the single-particle-size raw materials to obtain a particle size distribution curve, and performing fitting analysis on the particle size distribution curve to obtain the particle size ratio of the heat-conducting powder in the heat-conducting material. According to the analysis method for the formula of the heat-conducting powder in the heat-conducting material, quantitative analysis can be carried out on the formula, and the method has the advantages of being easy to operate, high in speed, small in error and high in efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal conductive materials, and in particular to an analysis method for a thermal conductive powder formula in a thermal conductive material. Background Art

[0002] Thermal conductive material is a polymer composite thermal conductive material that uses silicone oil resin as the bonding base material and achieves the purpose of thermal conductivity by filling thermal conductive powder. It includes thermal conductive gaskets, thermal conductive gel, thermal conductive silicone grease, thermal conductive adhesives, phase change materials, etc. It is mainly used for the transfer interface between electronic equipment and heat sinks or product casings, thereby achieving the important role of reducing the operating temperature of electronic equipment and extending the service life of electronic equipment. It has the advantages of easy use, high thermal conductivity, stable thermal conductivity, good compressibility, self-adhesion, high cleanliness, etc. It is an excellent thermal conductive material with a wide range of applications.

[0003] Thermal conductive materials generally consist of silicone oil, thermal conductive powder and other parts. The silicone oil is a polymer obtained by cross-linking vinyl silicone oil and hydrogen-containing silicone oil under the action of a catalyst; the powder is generally alumina powder or thermal conductive materials such as aluminum nitride and silicon carbide; other parts include catalysts that catalyze the cross-linking reaction of vinyl silicone oil and hydrogen-containing silicone oil, inhibitors that inhibit the catalytic effect, functional additives such as silane coupling agents, carbon black, graphite, graphene, silicon dioxide, titanium dioxide, etc.

[0004] With the development of the times, the electronic materials and electronic components used are required to have functions such as high frequency and high speed, large capacity storage and high-speed signal transmission. Such functions will cause a significant increase in the heat flux density of the chip. A large amount of heat energy can easily cause aging of electronic components and reduce the service life and reliability of the chip. Therefore, higher requirements are placed on thermal conductive materials. Domestic thermal conductive materials started late, especially in the field of semiconductor chips, where thermal conductive materials are still mainly imported. Therefore, more research needs to be invested in the field of thermal conductive materials. The most important performance of thermal conductive materials is thermal conductivity, which is mainly affected by the solid content and particle size ratio of the thermal conductive powder. The particle size ratio of the powder is complex, and it is difficult to directly obtain the particle size compound ratio information in the sample. Therefore, it is urgent to develop an analysis method for the powder particle size formula in the thermal conductive material, aiming to conveniently, accurately and quickly obtain the thermal conductive powder formula in an unknown sample. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an analysis method for the powder formula in the thermal conductive material. The method of the present invention can realize the quantitative analysis of the powder formula in the unknown thermal conductive material, and has the advantages of easy operation, small error, high efficiency and fast speed.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme:

[0007] (1) subjecting the thermally conductive material to solid-liquid extraction using an organic solvent, and filtering and separating the filtrate and the solid residue;

[0008] (2) adding hydrofluoric acid to the solid residue, stirring thoroughly and filtering, washing and drying the filter cake to obtain a thermally conductive powder;

[0009] (3) performing a particle size distribution test on the thermally conductive powder to obtain a particle size distribution curve, determining that the thermally conductive powder is a mixture of n single-particle size powders, the median particle size of the n-th single-particle size powder is the particle size classification corresponding to the n-th peak in the particle size distribution curve, where n is a natural number and n≥1;

[0010] (4) performing particle size distribution tests on the n kinds of single-particle-size powders respectively, constructing a fitted particle size distribution curve and fitting it with the particle size distribution curve in step (3), and analyzing and obtaining the formula of the thermally conductive powder in the thermally conductive material;

[0011] Furthermore, the thermally conductive material includes a silicone oil portion and a thermally conductive powder portion;

[0012] And / or, the thermally conductive material is preferably one of a thermally conductive gasket, thermally conductive silicone grease, thermally conductive gel, and thermally conductive adhesive;

[0013] And / or, the thermally conductive powder is one or more combinations of aluminum oxide, aluminum nitride or silicon carbide powder;

[0014] And / or, the median particle size D50 of the thermally conductive powder is greater than 1 μm.

[0015] Furthermore, the silicone oil part is a polymer obtained by cross-linking vinyl silicone oil and hydrogen-containing silicone oil under the action of a catalyst;

[0016] Furthermore, in step (1), the organic solvent comprises a mixture of one or more of dichloromethane, chloroform, tetrahydrofuran, toluene, and acetone; preferably a mixture of one or more of dichloromethane and tetrahydrofuran;

[0017] And / or, the solid-liquid extraction ratio is 2 to 20 mL of extraction solvent per gram of thermal conductive material, preferably 5 to 10 mL;

[0018] And / or, the solid-liquid extraction is performed 2 to 4 times, preferably 3 times;

[0019] Furthermore, in the step (2), the solid residue is dispersed by magnetic stirring with a dispersion solvent;

[0020] Further, the dispersion solvent includes a mixture of one or more of water, methanol, ethanol, n-propanol, isopropanol, acetonitrile, tetrahydrofuran, and acetone; preferably, the dispersion solvent is water;

[0021] And / or, each stirring time is 10 to 60 minutes, preferably 15 to 30 minutes;

[0022] And / or, the concentration of hydrofluoric acid is 35% to 50%; preferably 40% to 45%;

[0023] and / or, the ratio of the dispersion solvent to the hydrofluoric acid system is 0.2 to 5.0, preferably 0.5 to 2.0;

[0024] and / or, 1 to 20 mL, preferably 2 to 10 mL, more preferably 4 to 6 mL of hydrofluoric acid is required per gram of solid residue;

[0025] And / or, the stirring temperature is 10-40°C, preferably 20-30°C;

[0026] And / or, the water washing times are generally 3 times, each time using 10 mL;

[0027] And / or, the alcohol washing times are generally 3 times, each time using 10 mL; the alcohol washing solvent includes one or a combination of methanol and ethanol;

[0028] And / or, the drying temperature is 80-120°C;

[0029] And / or, the drying time is 30 to 60 minutes.

[0030] In the step (2), the purpose of adding hydrofluoric acid is to degrade the cross-linked silicone resin and remove the organic components modified on the surface of the powder, so that the powder becomes non-agglomerated and the particle size distribution test can be carried out reliably and effectively.

[0031] In step (2), the purpose of the standing operation is to allow the powder to naturally settle to the bottom, usually for 5 minutes; the purpose of pouring out most of the supernatant is to remove most of the hydrofluoric acid solution to facilitate subsequent filtration operations. The purpose of water washing is to remove residual hydrofluoric acid, and the purpose of alcohol washing is to remove residual water.

[0032] Furthermore, the step (4) comprises the following steps:

[0033] (4.1) The particle size distribution of the n single particle size powders is tested respectively to obtain a total of n particle size distribution curves of the single particle size powders. The particle size distribution curve Y of the nth single particle size powder is n =f n (x), where n is a natural number and n≥1, x represents the particle size classification in μm, and Y n Indicates volume density in %;

[0034] (4.2) Constructing the fitted particle size distribution curve Among them An Indicates the mass fraction of the nth single particle size powder;

[0035] (4.3) For the A in step (4.2) n Adjust until the fitted particle size distribution curve Y 拟合 The particle size distribution curve described in step (3) is basically consistent, and the number of portions A corresponding to each single particle size powder is obtained. n , thus obtaining the particle size ratio of the thermally conductive powder in the thermally conductive material.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) Compared with the qualitative analysis method of SEM scanning electron microscope, the present invention can realize the quantitative analysis of powder formula;

[0038] (2) After solid-liquid extraction of the thermal conductive material, the solid residue is treated with hydrofluoric acid to degrade the cross-linked silicone resin and remove the organic components modified on the surface of the powder, so that the thermal conductive powder to be tested no longer agglomerates, thereby improving the accuracy of subsequent particle size distribution testing;

[0039] (3) By testing the particle size distribution of existing single-particle-size powder and making a fitting comparison with the thermal conductive material to be tested, the particle size formula of the thermal conductive powder in the thermal conductive material to be tested can be quickly obtained, thereby improving the analysis efficiency and the accuracy of the analysis results. DETAILED DESCRIPTION

[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The present invention provides a method for preparing a thermally conductive pad, comprising the following steps:

[0042] (1) subjecting the thermally conductive material to solid-liquid extraction using an organic solvent, and filtering and separating the filtrate and the solid residue;

[0043] (2) adding hydrofluoric acid to the solid residue, stirring thoroughly and filtering, washing and drying the filter cake to obtain a thermally conductive powder;

[0044] (3) performing a particle size distribution test on the thermally conductive powder to obtain a particle size distribution curve, determining that there are n peaks in the particle size distribution curve and a particle size classification corresponding to each peak, thereby determining that the thermally conductive powder is a mixture of n single-particle size powders, the median particle size of the single-particle size powders is the particle size classification corresponding to the peak, and n is a natural number and n≥1;

[0045] (4) performing particle size distribution tests on n types of single particle size powders respectively to obtain particle size distribution curves, constructing fitted particle size distribution curves and fitting them with the particle size distribution curves described in step (3), and analyzing and obtaining the particle size ratio of the thermally conductive powder in the thermally conductive material.

[0046] <Thermal Conductive Materials>

[0047] The thermally conductive material described in the present invention can be a conventional thermally conductive material in the art such as a thermally conductive gasket, thermally conductive silicone grease, thermally conductive gel, and thermally conductive adhesive. The thermally conductive material includes an organic silicone oil part and a thermally conductive powder part. Further, in the embodiment of the present invention, the organic silicone oil part is a cross-linked product of vinyl silicone oil and hydrogen-containing silicone oil. The specific molecular structure formula and reaction process are as follows:

[0048]

[0049] In the present invention, the thermally conductive powder part of the thermally conductive material can be one or more of aluminum oxide, aluminum nitride, silicon carbide, etc.; further, in the embodiment of the present invention, the thermally conductive powder of the thermally conductive material is preferably aluminum oxide powder; the aluminum oxide powder can be modified aluminum oxide or non-modified aluminum oxide in the shape of sphere, angular shape, etc.;

[0050] The thermal conductive material of the present invention may further include a catalyst, an inhibitor, and functional additives such as a silane coupling agent, carbon black, graphite, graphene, silicon dioxide, titanium dioxide, etc.; further, the thermal conductive material in the embodiment of the present invention preferably has a catalyst of a Custer platinum catalyst and an inhibitor of diallyl maleate;

[0051] In the present invention, the median particle size of the single particle size powder in the thermally conductive powder is greater than 1 μm; for example, the thermally conductive powder is a mixture of one or more single particle size powders with a median particle size of 2 μm, 5 μm, 10 μm, 20 μm, 45 μm, 70 μm, 90 μm, 120 μm, etc.

[0052] <Organic Solvents>

[0053] In the present invention, the role of the organic solvent is to dissolve the part of the organic silicone oil that is not completely cross-linked in the thermally conductive material, thereby completing the preliminary separation of the powder part in the thermally conductive material; the organic solvent has the ability to dissolve silicone oil, and generally a medium-polarity solvent is selected, such as aromatic hydrocarbon solvents, halogenated hydrocarbon solvents, aliphatic hydrocarbons, ethers, ketones, ester solvents, etc., specifically for example, dichloromethane, chloroform, tetrahydrofuran, toluene, acetone, acetonitrile, carbon tetrachloride, benzene, ethyl acetate, etc.; in the embodiment of the present invention, one or more of dichloromethane, chloroform, tetrahydrofuran, toluene, and acetone are preferred, and one or more of dichloromethane and tetrahydrofuran are more preferred.

[0054] <Solid-Liquid Extraction>

[0055] In the present invention, the solid-liquid extraction is an operation of separating a solid mixture with a liquid or solvent, specifically, immersing the solid in a selected solvent, dissolving the easily soluble components in the solid into a solution, thereby achieving separation from the undissolved solid residue. In the present invention, the solid-liquid extraction process is to add an organic solvent to the thermal conductive material, dissolve it under magnetic stirring at room temperature, and then filter and separate to obtain a filter cake and a filtrate; the filter cake is the solid residue part of the thermal conductive material that cannot be dissolved in the solvent, mainly including a thermal conductive powder part and a completely cross-linked organic silicone oil part; the filtrate is a solution formed by the components of the thermal conductive material that are easily soluble in the organic solvent and the organic solvent.

[0056] In the present invention, the filtrate contains silicone oil resin dissolved in an organic solvent, specifically incompletely cross-linked polydimethylsiloxane; the silicone oil resin in the filtrate can be measured by gel permeation chromatography (GPC) to determine its molecular weight and molecular weight distribution, and the gel permeation chromatography test parameters are:

[0057] Chromatographic column: Agilent PLgel single pore size column, part number PL1110-6530, 7.5×300mm, with guard column, part number PL110-1520, 7.5×50mm;

[0058] Column temperature: 40°C;

[0059] Mobile phase: chromatography grade tetrahydrofuran;

[0060] Mobile phase flow rate: 0.7 ml / min;

[0061] Detector: differential detector;

[0062] Sample injection volume: 20 μL.

[0063] In the present invention, the solid residue includes the thermally conductive powder portion and the silicone oil portion that is not dissolved by the organic solvent in step (1), specifically the fully cross-linked silicone oil portion;

[0064] In step (1) of the present invention, an organic solvent dissolves the organic components in the thermally conductive material, and the filtrate and the solid residue are separated by filtration, thereby achieving preliminary separation of the inorganic thermally conductive powder part in the thermally conductive material.

[0065] <Dispersion Solvent>

[0066] In the present invention, the dispersing solvent is used to disperse the solid residue, and generally a solvent miscible with water is selected, including one or a mixture of water, alcohol solvents, tetrahydrofuran, acetonitrile, and acetone; the alcohol solvent includes methanol, ethanol, n-propanol, isopropanol and other conventional alcohol solvents in the art; in the embodiment of the present invention, water is preferably used as the dispersant;

[0067] In step (2) of the present invention, the stirring time is selected as the time for the powder to be evenly dispersed, which is generally selected as 10 to 60 minutes, and more preferably 15 to 30 minutes; in the embodiment of the present invention, it is preferably 30 minutes;

[0068] After extensive research, the inventors found that hydrofluoric acid can not only decompose the cross-linked silicone oil part, but also remove the organic components modified on the surface of the powder. At the same time, its reaction activity with the thermal conductive powder part is relatively small. Therefore, adding hydrofluoric acid treatment can make the powder non-agglomerated, so that the particle size distribution test can be carried out reliably and effectively.

[0069] At the same time, the inventors found in the study that improper use of hydrofluoric acid will also cause certain corrosion to the powder, destroy the original shape of the powder, and even affect the particle size of the powder, resulting in poor accuracy of the test results. Therefore, further, the hydrofluoric acid concentration described in step (2) of the present invention is controlled at 35% to 50%, preferably 40% to 45%; the ratio of the dispersing solvent to the hydrofluoric acid system is 0.2 to 5.0, preferably 0.5 to 2.0; 1 to 20 mL of hydrofluoric acid is required per gram of sample, preferably 2 to 10 mL, and more preferably 4 to 6 mL; the stirring temperature is 10-40°C, preferably 15-30°C, and more preferably 25°C.

[0070] In step (2) of the present invention, the standing operation is to allow the thermally conductive powder to naturally settle to the bottom, usually for 5 minutes; the pouring of most of the supernatant is to remove most of the hydrofluoric acid solution to facilitate subsequent filtering operations. The purpose of water washing is to remove residual hydrofluoric acid, and the purpose of alcohol washing is to remove residual water. The water washing number is generally 3 times, and the amount used each time is 10 mL; the alcohol washing number is generally 3 times, and the amount used each time is 10 mL; the alcohol is methanol, ethanol and other alcohol solvents commonly used by those skilled in the art.

[0071] In step (2) of the present invention, the drying temperature is 80-120° C. and the drying time is 30-60 min.

[0072] <Particle size distribution test>

[0073] In the embodiment of the present invention, the instrument used for the particle size distribution test is a Mastersizer laser particle size analyzer. After adding an appropriate amount of sample, the analysis and detection system of the instrument is started, and finally the particle size distribution data of the sample to be tested and the corresponding particle size distribution curve are obtained. In the particle size distribution curve of the present invention, the horizontal axis is the particle size classification, in μm; the vertical axis is the volume concentration, in %;

[0074] The inventors found in their research that the particle size distribution curve of the thermally conductive powder obtained after the hydrofluoric acid treatment can reflect the real powder formula information. The particle size classification corresponding to the peak in the particle size distribution curve of step (3) of the present invention is the median particle size of the single particle size powder in the thermally conductive powder. For example, if there are two peaks in the particle size distribution curve, corresponding to the particle size classifications of 2μm and 20μm, it means that the thermally conductive powder is partially composed of two powders with median particle sizes of 2μm and 5μm, respectively. If there are n peaks, it means that the thermally conductive powder is a mixture of n single particle size powders, wherein the median particle size of each powder is the particle size classification corresponding to the corresponding peak. Therefore, the particle size distribution curve measured in step (3) of the present invention can obtain information on which single particle size powder raw materials the thermally conductive powder is mixed from.

[0075] <Fitting Analysis>

[0076] In step (4) of the present invention, the fitting analysis is to use the particle size distribution of the existing single particle size powder raw material to make a fitting comparison with the unknown sample to analyze the powder formula of the unknown sample. The specific steps are as follows:

[0077] (4.1) Perform particle size distribution tests on n single particle size powders respectively, and obtain the particle size distribution curve Y of the nth single particle size powder respectively. n =f n (x), where n is a natural number and n≥1, x represents the particle size classification in μm, and Y n Indicates volume density in %;

[0078] (4.2) Constructing the fitted particle size distribution curve Among them A n Indicates the mass fraction of the nth single particle size powder;

[0079] (4.3) For the A in step (4.2) n Adjust until the particle size distribution curve Y fits 拟合 The particle size distribution curve described in step (3) is basically consistent, and the number of portions A corresponding to each single particle size powder is obtained. n , thus obtaining the particle size ratio of the thermally conductive powder in the thermally conductive material.

[0080] In step (4) of the present invention, the n kinds of particle sizes analyzed in step (3) are first subjected to particle size distribution tests to obtain particle size distribution curves of n kinds of single particle size powder raw materials, wherein the particle size distribution curve of the nth single particle size powder is Y n =f n (x); Use the particle size distribution curves of n single particle size powder raw materials to construct a fitted particle size distribution curve Among them A n represents the number of nth particle size in the thermally conductive powder; n Adjustments are made until the particle size distribution constructed for the fit analysis The particle size distribution is basically consistent with the particle size distribution described in step (3), and the A corresponding to each single particle size powder raw material is obtained. n , thus obtaining the particle size ratio of the thermally conductive powder in the thermally conductive material. BRIEF DESCRIPTION OF THE DRAWINGS

[0081] Figure 1 This is a related analysis test diagram in Example 1 of the present invention: Figure 1 (a) is a comparison of the particle size distribution curves of alumina powder (45μm: 5μm = 2:1) after physical mixing (red) and making into thermal conductive material and treating with hydrofluoric acid (green); Figure 1 (b) is the particle size distribution curve measured after the powder is made into a thermal conductive material but not treated with hydrofluoric acid; Figure 1 (c) is a comparison chart of the fitted particle size distribution curve (red) and the particle size distribution curve of the thermal conductive material after being treated with hydrofluoric acid (blue).

[0082] Figure 2 This is the analysis test diagram related to Example 2 of the present invention: Figure 2 (a) is a comparison of the particle size distribution curves of alumina powder (90μm: 20μm: 5μm = 3:1:2) after physical mixing (red) and making into thermal conductive material and treating with hydrofluoric acid (green); Figure 2 (b) is the particle size distribution curve measured after the powder is made into a thermal conductive material but not treated with hydrofluoric acid; Figure 2 (c) is a comparison chart of the fitted particle size distribution curve (red) and the particle size distribution curve of the thermal conductive material after being treated with hydrofluoric acid (blue).

[0083] Figure 3 Related analysis test diagrams in Example 3 of the present invention: Figure 3 (a) is a comparison of the particle size distribution curves of alumina powder (90μm: 20μm: 5μm: 2μm = 3:1:1.5:0.5) after physical mixing (red) and making into thermal conductive material and treating with hydrofluoric acid (green); Figure 3 (b) is the particle size distribution curve measured after the powder is made into a thermal conductive material but not treated with hydrofluoric acid; Figure 3(c) is a comparison chart of the fitted particle size distribution curve (red) and the particle size distribution curve of the thermal conductive material after being treated with hydrofluoric acid (blue).

[0084] Example

[0085] The present invention is described below with reference to the following examples, but the present invention is not limited to the following examples.

[0086] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0087] Preparation Example 1: Preparation of thermal conductive material DH-P1:

[0088] Vinyl silicone oil, hydrogenated silicone oil, thermally conductive powder, catalyst, inhibitor and other additives are added to a mixing device and dispersed and vacuumed. After uniform dispersion, a thermally conductive mixture is obtained and cured at 140°C for 2 hours. The mass fractions of each component are: 7.5 parts of vinyl silicone oil (viscosity 950mPa.s), 0.5 parts of hydrogenated silicone oil (viscosity 200mPa.s); 45um median particle size (D 50 =45μm) of Al2O3 powder 61.3 parts, 5μm median particle size (D 50 =5μm) Al2O3 powder 30.7 parts; Custer catalyst 0.008 parts, inhibitor diallyl maleate 0.002 parts, nano carbon black 0.06 parts.

[0089] The operating steps of the mixing device are as follows:

[0090] (1) Weigh thermal conductive powders of different particle sizes in a mixing container 1, place them in an auto-rotator with a counterweight, adjust the revolution speed to 1000 r / min, the rotation speed to 600 r / min, evacuate and mix for 3 min at an absolute pressure of ≤20 Pa;

[0091] (2) Weigh vinyl silicone oil, catalyst, inhibitor and other additives in mixing container 2, put them into the auto-rotator with a counterweight, adjust the revolution speed to 1000 r / min and the rotation speed to 600 r / min, evacuate and mix for 3 min under the condition of absolute pressure ≤ 20 Pa; then add hydrogen-containing silicone oil, put them into the auto-rotator with a counterweight, and mix for 3 min under the same conditions;

[0092] (3) Add the mixed thermally conductive powder in container 1 to container 2, place the mixture in an auto-rotation machine with a counterweight, adjust the revolution speed to 1500 r / min and the rotation speed to 900 r / min, evacuate the mixture and mix for 3 minutes at an absolute pressure of ≤20 Pa; repeat the auto-rotation condition 3 times to obtain a uniformly dispersed thermally conductive mixture.

[0093] Preparation Example 2: Preparation of thermal conductive material DH-P2:

[0094] The experimental steps of this preparation example are the same as those of Preparation Example 1, except that the powder types and proportions of this preparation example are different. The mass fractions of each component are: 7.5 parts of vinyl silicone oil (viscosity 950mPa.s), 0.5 parts of hydrogenated silicone oil (viscosity 200mPa.s); 90um median particle size (D 50 =90μm) of Al2O3 powder 46.0 parts, 20um median particle size (D 50 =20μm) of Al2O3 powder 15.3 parts, 5μm median particle size (D 50 =5μm) Al2O3 powder 30.7 parts; Custer catalyst 0.008 parts, inhibitor diallyl maleate 0.002 parts, nano carbon black 0.06 parts.

[0095] Preparation Example 3: Preparation of thermal conductive material DH-P3:

[0096] The experimental steps of this preparation example are the same as those of Preparation Example 1, except that the powder types and proportions of this preparation example are different. The mass fractions of each component are: 7.5 parts of vinyl silicone oil (viscosity 950mPa.s), 0.5 parts of hydrogenated silicone oil (viscosity 200mPa.s); 90μm median particle size (D 50 =90μm) of Al2O3 powder 46.0 parts, 20μm median particle size (D 50 =20μm) of Al2O3 powder 15.3 parts, 5μm median particle size (D 50 =5μm) of Al2O3 powder 23.0 parts, 2μm median particle size (D 50 =2μm) Al2O3 powder 7.7 parts; Custer catalyst 0.008 parts, inhibitor diallyl maleate 0.002 parts, nano carbon black 0.06 parts.

[0097] Example 1

[0098] (1) Weigh 5.004 g of the thermal conductive material DH-P1 into a 100 mL single-mouth glass flask, add 50 mL of dichloromethane and stir magnetically at room temperature for 30 min, filter the solid residue, and continue to extract the filter cake with 50 mL of dichloromethane for two times. The combined dichloromethane filtrate is concentrated and dried to obtain 0.305 g of a colorless oily liquid. The filter cake is dried and weighed to 4.690 g. The particle size distribution of the filter cake is measured using a particle size tester. The results are as follows: Figure 1 (b)

[0099] (2) Take 4.690g of the dried filter cake powder and put it into a 100mL plastic centrifuge tube. Add 20mL of water and disperse it by magnetic stirring. Then add 20mL of hydrofluoric acid (40% concentration) and stir it magnetically at room temperature for 30min. Let it stand for 5min and pour off the supernatant. Filter, wash the filter cake 3 times with 10mL of water and 3 times with 10mL of methanol, and dry it at 100℃ for 30min. Obtain 4.541g of thermal conductive powder.

[0100] (3) Take the dried thermal conductive powder and measure the particle size distribution to obtain the particle size distribution curve of the thermal conductive powder. The results are as follows: Figure 1 As shown in (a), the peaks in the particle size distribution curve correspond to the particle size classifications of 5μm and 45μm respectively. At the same time, the particle size distribution of the thermal conductive powder mixture in step (1) (61.3 parts of Al2O3 powder with a median particle size of 45μm and 30.7 parts of Al2O3 powder with a median particle size of 5μm) was compared. The comparison results are shown in FIG. Figure 1 (a) shown.

[0101] (4) Particle size distribution tests were performed on Al2O3 powder with a median particle size of 45 μm and Al2O3 powder with a median particle size of 5 μm to obtain particle size distribution curves Y1=f1(x) and Y2=f2(x); and a fitted particle size distribution curve was constructed. The A1 and A2 are adjusted until the particle size distribution curve Y 拟合 The particle size distribution curve obtained after the hydrofluoric acid treatment in step (3) is basically consistent. At this time, the Al2O3 powder formula of the thermal conductive material is 45μm:5μm=A1:A2. Take A1=2, A2=1 for verification, and obtain the fitted particle size distribution curve, which is compared with the particle size distribution curve of the powder after the hydrofluoric acid treatment. The comparison results are as follows: Figure 1 (c) as shown.

[0102] Example 2

[0103] (1) Weigh 5.007 g of the thermal conductive material DH-P2 into a 100 mL single-mouth glass flask, add 50 mL of dichloromethane and stir magnetically at room temperature for 30 min, filter the solid residue, and continue to extract the filter cake with 50 mL of dichloromethane for two times. The combined dichloromethane filtrate is concentrated and dried to obtain 0.310 g of a colorless oily liquid. The filter cake is dried and weighed to 4.684 g. The particle size distribution of the filter cake is measured using a particle size tester. The results are as follows: Figure 2 (b)

[0104] (2) Take 4.684g of dried filter cake powder and put it into a 100mL plastic centrifuge tube. Add 20mL of water and disperse it by magnetic stirring. Then add 20mL of hydrofluoric acid aqueous solution (40% concentration) and stir it magnetically at room temperature for 30min. Let it stand for 5min and pour out the supernatant. Filter, wash the filter cake with 10mL of water 3 times, wash it with 10mL of methanol 3 times, and dry it at 100℃ for 30min. Obtain 4.551g of thermal conductive powder.

[0105] (3) Take the dried thermal conductive powder and measure the particle size distribution to obtain the particle size distribution curve of the thermal conductive powder. The results are as follows: Figure 2 As shown in (a), the peaks in the particle size distribution curve correspond to the particle size classifications of 5 μm, 20 μm and 90 μm respectively. 50 =90μm) of Al2O3 powder 46.0 parts, 20μm median particle size (D 50 =20μm) of Al2O3 powder 15.3 parts, 5μm median particle size (D 50 =5μm) of Al2O3 powder 30.7 parts) measured the particle size distribution for comparison, the comparison results are as follows Figure 2 (a) shown.

[0106] (4) Particle size distribution tests were performed on Al2O3 powder with a median particle size of 90 μm, Al2O3 powder with a median particle size of 20 μm, and Al2O3 powder with a median particle size of 5 μm, respectively, to obtain particle size distribution curves Y1=f1(x), Y2=f2(x), and Y1=f3(x); a fitted particle size distribution curve was constructed Adjust A1, A2, and A3 until the particle size distribution curve Y 拟合 The particle size distribution curve obtained after the hydrofluoric acid treatment in step (3) is basically consistent. At this time, the Al2O3 powder formula of the thermal conductive material is 90μm: 20μm: 5μm = A1: A2: A3. Take A1 = 3, A2 = 1, A3 = 2 for verification, and obtain the fitted particle size distribution curve, which is compared with the particle size distribution curve of the powder after the hydrofluoric acid treatment. The comparison results are as follows: Figure 2 (c) as shown.

[0107] Example 3

[0108] (1) Weigh 6.005 g of the thermal conductive material DH-P3 into a 100 mL single-mouth glass flask, add 50 mL of dichloromethane and stir magnetically at room temperature for 30 min, filter the solid residue, and continue to extract the filter cake with 50 mL of dichloromethane for two times. The combined dichloromethane filtrate is concentrated and dried to obtain 0.362 g of a colorless oily liquid. The filter cake is dried and weighed to 5.638 g. The particle size distribution of the filter cake is measured using a particle size tester. The results are as follows: Figure 3 (b)

[0109] (2) Take 5.638g of the dried filter cake powder and put it into a 100mL polytetrafluoroethylene centrifuge tube, add 20mL of water, disperse it by magnetic stirring, then add 20mL of hydrofluoric acid aqueous solution (40% concentration), and stir it magnetically at room temperature for 30min. Let it stand for 5min, pour off the supernatant. Filter, wash the filter cake with 10mL of water 3 times, wash it with 10mL of methanol 3 times, and dry it at 100℃ for 30min. Obtain 5.447g of thermal conductive powder.

[0110] (3) Take the dried thermal conductive powder and measure the particle size distribution to obtain the particle size distribution curve of the thermal conductive powder. The results are as follows: Figure 3 As shown in (a), the peaks in the particle size distribution curve correspond to the particle size classifications of 2 μm, 5 μm, 20 μm and 90 μm respectively. 50 =90μm) of Al2O3 powder 46.0 parts, 20μm median particle size (D 50 =20μm) of Al2O3 powder 15.3 parts, 5μm median particle size (D 50 =5μm) of Al2O3 powder 23.0 parts, 2um median particle size (D 50 =2μm) of Al2O3 powder 7.7 parts) measured the particle size distribution and compared them. The comparison results are as follows Figure 3 (a) shown.

[0111] (4) Particle size distribution tests were performed on Al2O3 powder with a median particle size of 90 μm, Al2O3 powder with a median particle size of 20 μm, Al2O3 powder with a median particle size of 5 μm, and Al2O3 powder with a median particle size of 2 μm, respectively, to obtain particle size distribution curves Y1=f1(x), Y2=f2(x), Y3=f3(x), and Y4=f4(x); and a fitted particle size distribution curve was constructed. Adjust A1, A2, A3, and A4 until the fitted particle size distribution Y 拟合 The particle size distribution is basically consistent with the particle size distribution described in step (3). At this time, the Al2O3 powder formula of the thermal conductive material is 90μm: 20μm: 5μm: 2μm = A1: A2: A3: A4. Take A1 = 3, A2 = 1, A3 = 1.5, A4 = 0.5 for verification, and obtain the fitted particle size distribution curve, which is compared with the particle size distribution curve of the powder after hydrofluoric acid treatment. The comparison results are as follows: Figure 3 (c) as shown.

[0112] according to Figure 1 (b) Figure 2 (b) Figure 3(b) The data given by the particle size distribution curve shows that the particle size distribution is above 100μm, which is very different from the raw materials used. Therefore, it is meaningless to directly measure the particle size distribution of thermal conductive materials that have not been treated with hydrofluoric acid. The particle size distribution shown cannot reflect the actual particle size distribution of thermal conductive powders. This is because there are organic components such as fully cross-linked silicone oil parts that have not been extracted by organic solvents in the test sample, which causes the thermal conductive powder to agglomerate. After hydrofluoric acid treatment, the particle size distribution test is performed again, and the results are as follows: Figure 1 (a) Figure 2 (a) Figure 3 As shown in (a), it is basically consistent with the particle size distribution curve measured by using the thermal conductive powder raw material mixture in the same proportion, proving that the agglomerated thermal conductive powder can be dispersed by hydrofluoric acid treatment, restoring the actual particle size distribution of the thermal conductive powder, thereby improving the accuracy of the powder particle size formula quantification.

[0113] like Figure 1 (c) Figure 2 (c) Figure 3 (c) shows that the fitting result analysis shows that the fitting method adopted by the present invention can quickly and relatively accurately obtain the particle size formula of the thermal conductive powder, and the fitting curve under the theoretical value of the particle size ratio is basically consistent with the particle size distribution curve measured after the sample to be tested is treated with hydrofluoric acid, thereby proving that the analysis method of the present invention can relatively quickly and accurately obtain the powder formula of the sample to be tested, with small error, fast speed and good operability.

[0114] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A method for analyzing the formula of thermally conductive powder in a thermally conductive material, characterized in that: The steps include: (1) subjecting the thermally conductive material to solid-liquid extraction using an organic solvent, and filtering and separating the filtrate and the solid residue; (2) adding hydrofluoric acid to the solid residue, stirring thoroughly and filtering, washing and drying the filter cake to obtain a thermally conductive powder; (3) performing a particle size distribution test on the thermally conductive powder to obtain a particle size distribution curve, determining that the thermally conductive powder is a mixture of n single-particle size powders, the median particle size of the n-th single-particle size powder is the particle size classification corresponding to the n-th peak in the particle size distribution curve, where n is a natural number and n≥1; (4) performing particle size distribution tests on the n kinds of single particle size powders respectively to obtain particle size distribution curves, constructing fitted particle size distribution curves to fit the particle size distribution curves in step (3), and analyzing to obtain the formula of the thermally conductive powder in the thermally conductive material.

2. According to the method of claim 1, the step (4) specifically comprises: (4.1) The particle size distribution of the n single particle size powders is tested respectively, and the particle size distribution curve of the n single particle size powder is Y n =f n (x), where n is a natural number and n≥1, x represents the particle size classification in μm, and Y n Indicates volume density in %; (4.2) Constructing the fitted particle size distribution curve Among them A n Indicates the mass fraction of the nth single particle size powder; (4.3) For the A in step (4.2) n Adjust until the fitted particle size distribution curve Y 拟合 The particle size distribution curve described in step (3) is basically consistent, and the mass fraction A corresponding to each single particle size powder is obtained. n , thus obtaining the formula of thermal conductive powder in thermal conductive material.

3. The method according to claim 1 or 2, characterized in that: The thermally conductive material comprises a silicone oil part and a thermally conductive powder part; the thermally conductive material is preferably one of a thermally conductive gasket, thermally conductive silicone grease, thermally conductive gel, and a thermally conductive adhesive.

4. The method according to claim 3, characterized in that: The thermally conductive powder is one or more combinations of aluminum oxide, aluminum nitride or silicon carbide powder; and / or the silicone oil part is a cross-linked product of vinyl silicone oil and hydrogen-containing silicone oil.

5. The method according to any one of claims 1 to 4, characterized in that: The median particle size D50 of the thermally conductive powder is greater than 1 μm.

6. The method according to any one of claims 1 to 5, characterized in that: The organic solvent in step (1) includes one or more combinations of dichloromethane, chloroform, tetrahydrofuran, toluene, and acetone; and / or the solid-liquid extraction ratio in step (1) is 2 to 20 mL of extraction solvent per gram of thermal conductive material; and the number of solid-liquid extractions is 2 to 4 times.

7. The method according to any one of claims 1 to 6, characterized in that: The step (2) further comprises the following steps: dispersing the solid residue with a dispersing solvent by magnetic stirring, adding hydrofluoric acid thereto, stirring thoroughly, standing, pouring off most of the supernatant, filtering, washing the filter cake with water, washing with alcohol, and drying to obtain a thermally conductive powder.

8. The method according to claim 7, wherein the dispersing solvent comprises one or more combinations of water, methanol, ethanol, n-propanol, isopropanol, acetonitrile, tetrahydrofuran, and acetone; and / or the stirring time is 10 to 60 minutes; and / or the drying temperature is 80 to 120° C. and the time is 30 to 60 minutes.

9. The method according to claim 7 or 8, characterized in that: The volume ratio of the dispersion solvent to hydrofluoric acid is 0.2 to 5.0, preferably 0.5 to 2.

0.

10. The method according to any one of claims 1 to 9, wherein the concentration of hydrofluoric acid is 35% to 50%, preferably 40% to 45%; and / or 1 to 20 mL of hydrofluoric acid is required per gram of solid residue, preferably 2 to 10 mL, more preferably 4 to 6 mL.

Citation Information

Patent Citations

  • Cross-scale broad-spectrum particle size plugging formula granularity analysis method

    CN110044782A

  • Aluminum nitride and aluminum oxide compounded heat-conducting insulating silica gel material and preparation method thereof

    CN111925654A

  • Method for regenerating silicon

    JP2010070425A

  • Hollow silica particle and method for producing the same

    JP2020083736A

  • Analysis method

    US20230280256A1